Genome-wide identification, phylogenetic analysis, and expression profiling of the BBX family genes in pear. Issue 1 (2nd January 2018) - Zou, Zhiyan; Wang, Rihong; Wang, Ran; Yang, Shaolan; Yang, Yingjie
ABSTRACT: B-box containing proteins (BBXs) are a class of zinc finger transcription factor proteins that contain one or two B-box domains and play important roles in plant growth and development. The BBX gene family has been identified in the Arabidopsis and rice genomes. However, no comprehensive identification has been reported in pear. In this study, 37 genes were identified as candidate BBX s in Chinese white pear ( Pyrus bretschneideri Rehd) and denominated following the uniform nomenclature in Arabidopsis . We also performed analyses of their phylogenic relationships, structures, chromosomal locations, promoter regions, Gene Ontology (GO) annotations, and expression patterns. The identified genes were classified into five groups based on phylogeny and domain constitution analysis. PbBBXs were unevenly distributed in 12 out of 17 pear chromosomes. The cis -elements in the promoters of PbBBX s were mainly related to light, stress, and hormone response. Gene expression analysis by quantitative real-time PCR showed that PbBBX s had differential expression in different plant organs and could be classified into four major groups. PbBBX s also showed differential responses to low temperature and dehydration treatments. Overall, this study provided useful information for further functional analysis of BBX s in pear.